Gated electron transfer of cytochrome c6 at biomimetic interfaces: a time-resolved SERR study - Kranich, Anja (2009)
The electron shuttle heme protein Cyt-c6 from the photosynthetic cyanobacterium Nostoc sp. PCC 7119 was immobilized on nanostructured Ag electrodes coated with SAMs that mimic different possible interactions with its natural reaction partner PSI. The structure, redox potential, and electron-transfer dynamics of the SAM-Cyt-c6 complexes were investigated by TR-SERR spectroelectrochemistry. It is shown that the heterogeneous electron-transfer process is gated both in electrostatic and hydrophobic-hydrophilic complexes. At long tunneling distances, the reaction rate is controlled by the tunneling probability, while at shorter distances or higher driving forces, protein dynamics becomes the rate-limiting event.